Pengaruh Pendidikan Dan Pelatihan Terhadap Peningkatan Kinerja Pegawai Pada Kantor Badan Pengelola Keuangan Daerah Kabupaten Enrekang - Ruspratiwi Ruspratiwi; Agung Widhi Kurniawan; Burhanuddin Burhanuddin; Hj. Siti Hasbiah; Uhud Darmawan Natsir (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
the This research aims to analyze the influence of education and training on improving employee performance. The sample used in this research was 30 employees of the Enrekang Regency Regional Financial Management Agency. The data collection technique used in this research used observation and questionnaire methods. The analysis technique used in this research is multiple linear regression using Statistical Product and Service Solution (SPSS). The results of this research are that employee education (X1) has a positive and significant effect on the performance of employees of the Enrekang Regency Regional Financial Management Agency. Employee training (X2) has a positive and significant effect on the performance of Enrekang Regency Regional Financial Management Agency employees. Employee education (X1) and training (X2) have a positive and significant effect on employee performance (Y) of the Regional Financial Management Agency of Enrekang Regency.